Delayed Progressive Mass Effect After Secured Ruptured Middle Cerebral Artery Aneurysm: Risk Factors and Outcomes - Li, Ying-Ching; Chen, Ching-Chang; Chen, Chun-Ting; Tu, Po-Hsun; Yeap, Mun-Chun; Wu, Yi-Ming; Liu, Zhuo-Hao; Chang, Ting-Wei; Lin, Ya-Jui; Wu, Tai-Wei Erich; Hsieh, Po-Chuan (Frontiers in Surgery, 2022)
Objective: Delayed progressive mass effect (DPME) after securing an aneurysm is uncommon following microsurgical or endovascular repair and leads to a poor clinical outcome. Patients with ruptured middle cerebral artery (MCA) aneurysms have a high risk of postoperative oedema and mass effect, which may require decompressive treatment. Because few studies have discussed the risk and predictive factors, we focused on patients with ruptured MCA aneurysms and evaluated the outcomes of these patients and the necessity of salvage surgery when DPME was presented. Methods: Data on 891 patients with aneurysmal subarachnoid haemorrhage (aSAH) treated between January 2011 and February 2020 were extracted from the medical database of a tertiary referral centre. A total of 113 patients with aSAH resulting from at least one MCA aneurysm were identified. After excluding patients with several clinical confounders, we enrolled 80 patients with surgically treated aSAH. We examined the morphological characteristics of aneurysms and hematomas, perioperative contrast pooling patterns, presence of distal hematomas, perisylvian low density, occlusive treatment modality, management strategies, the need for salvage surgical decompression for an intracranial mass effect, and postoperative 90-day outcomes to identify possible risk factors. Results: DPME was observed in 27 of the 80 patients (33.7%). The DPME and non-DPME group differed significantly in some respects. The DPME group had a higher risk of salvage surgery (p < 0.001) and poorer outcomes (mRS at day 90; p = 0.0018). The univariate analysis indicated that the presence of hematoma, CTA spot signs, perisylvian low density, and distal hematoma were independent risk factors for DPME. We also noted that DPME remained an independent predictor of a poorer 90-day functional outcome (mRS ≤ 2). Conclusion: DPME can lead to salvage decompression surgery and directly relates to poor outcomes for patients with a ruptured MCA aneurysm. Distal hematoma, perisylvian low density, and CTA spot signs on preoperative images can predict DPME.